Tenure and management of non-state forests in China since 1950: a historical review - Liu Dachang (2001)
This article reviews the policies for the tenure and management of non-state forests that have undergone fundamental changes in China since the early 1950s. Private ownership and household management that were dominant in 1950-55 gave way to collectivization in 1956. Collective management remained dominant until reforms in the early 1980s. Since that time, rapid changes in tenure and management policy have given households more control over tree and forest resources. However, this high frequency of policy change causes a complete lack of confidence on villagers in tenure security. This has encouraged the rapid conversion of forest resources by farmers. The government and forest departments responded by promoting various shareholding systems and farmer households are also trying out new forms of collaboration of one kind or another. Empirical evidence shows that self-initiating shareholder systems created on voluntary basis perform better than those shareholding systems that are merely disguised form of former collective management. They build on existing, local, social capital and farmers are able to participate in making decision about planning, management activities, product use, and income distribution, which is the core of local forest management. Even so this is not sufficient to achieve the desired results in the case of timber trees. These trees are subject to many regulations that discourage investment in them. It is critical to vest villagers with full rights to their trees. China should apply separate regulations to natural forests and artificial plantations that are established from now on.